Exploitation of Inland-Breeding Antarctic Petrels by South Polar Skuas - Brooke, Michael de L; Keith, Dave; Røv, Nils (Oecologia, 1999)
During the austral summer of 1996/1997 we studied south polar skuas at Svarthamaren, Dronning Maud Land, Antarctica, where the world's largest known colony of Antarctic petrels is found. Our censuses suggested approximately 250 full-grown skuas and 140,000 breeding pairs of petrels were present. During their breeding season, skuas did not visit the open sea at least 200 km from the site; they relied entirely on prey caught and scavenged from the petrel colony. Because the site is so isolated, we asked whether the prey (petrels) had swamped the predators (skuas), or whether there was evidence that predator numbers were limited by the size of the prey population. Particularly at the end of the petrel incubation period, we found a close correspondence between the energy required by adult skuas and their chicks, ascertained from time budget studies, and the rate at which petrel eggs disappeared from the colony. This suggests that, in this closed system, the predator population was limited by the prey population, and that predator swamping was not an advantage that petrels gained by nesting in this remote location.
Publisher: Springer
Keywords: Dronning Maud Land; NARE 1996/97; fugler; ornitologi; petreller; zoologi

Meltwater production in Antarctic blue-ice areas: sensitivity to changes in atmospheric forcing - Liston, Glen E.; Bruland, Oddbjørn; Winther, Jan-Gunnar; Elvehøy, Hallgeir; Sand, Knut (Polar Research, 1999)
In the near coastal regions of Dronning Maud Land, Antarctica, below-surface ice-melt in blue-ice areas has been observed. The low scattering coefficients of the large-grained blue-ice allow penetration of solar radiation, thus providing an energy source below the ice surface. The sub-surface meltwater is significant enough to show up on remote-sensing imagery in the form of ice-covered lakes. Adjacent snow-accumulation areas have much higher scattering coefficients and consequently limit solar radiation penetration in these regions. These snow and ice surfaces are generally below freezing, and little surface melting occurs. To assess the response of these melt features to changes in atmospheric forcings such as cloudiness, air temperature, and snow accumulation, a physically-based model of the coupled atmosphere, radiation, snow, and blue-ice system has been developed. The model consists of a heat transfer equation with a spectrally-dependent solar-radiation source term. The penetration of radiation into the snow and blue-ice depends on the surface albedo, and the snow and blue-ice grain size and density. Model simulations show that ice melt occurring in this area is sensitive to potential variations in atmospheric forcing. Under certain conditions more traditional surface melting occurs and, under other conditions, the existing melt processes can be shut down completely. In light of the sensitivity of this system to variations in atmospheric forcing, and the ability to view melt-related features using remote sensing, a tool exists to efficiently monitor variations in Antarctic coastal climate.
Keywords: Dronning Maud Land; NARE 1996/97; blåis; glasiologi; innlandsis; isshelf; smelting

Below-surface ice melt on the coastal Antarctic ice sheet - Liston, Glen E; Winther, Jan-Gunnar; Bruland, Oddbjørn; Elverhøy, Hallgeir; Sand, Knut (Journal of Glaciology, 1999)
In the Jutulgryta area of Dronning Maud Land, Antarctica, subsurface melting of the ice sheet has been observed. The melting takes place during the summer months in blue-ice areas under conditions of below-freezing air and surface temperatures. Adjacent snow-covered regions, having the same meteorological and climatic conditions, experience little or no subsurface melting. To help explain and understand the observed melt-rate differences in the blue-ice and snow-covered areas, a physically based numerical model of the coupled atmosphere, radiation, snow and blue-ice system has been developed. The model comprises a heat-transfer equation which includes a spectrally dependent solar-radiation source term. The penetration of radiation into the snow and blue ice depends on the solar-radiation spectrum, the surface albedo and the snow and blue-ice grain-sizes and densities. In addition, the model uses a complete surface energy balance to define the surface boundary conditions. It is run over the full annual cycle, simulating temperature profiles and melting and freezing quantities throughout the summer and winter seasons. The model is driven and validated using field observations collected during the Norwegian Antarctic Research Expedition (NARE) 1996–97. The simulations suggest that the observed differences between subsurface snow and blue-ice melting can be explained largely by radiative and heat-transfer interactions resulting from differences in albedo, grain-size and density between the two mediums.
Keywords: Dronning Maud Land; NARE 1996/97; blåis; geofysikk; glasiologi; innlandsis

Climate variables along a traverse line in Dronning Maud Land, East Antarctica - van den Broeke, Michiel R; Winther, Jan-Gunnar; Isaksson, Elisabeth; Pinglot, Jean Francis; Karlöf, Lars; Eiken, Trond; Louk, Conrads (Journal of Glaciology, 1999)
Temperature, density and accumulation data were obtained from shallow firn cores, drilled during an overland traverse through a previously unknown part of Dronning Maud Land, East Antarctica. The traverse area is characterised by high mountains that obstruct the ice flow, resulting in a sudden transition from the polar plateau to the coastal region. The spatial variations of potential temperature, near-surface firn density and accumulation suggest that katabatic winds are active in this region. Proxy wind data derived from firn-density profiles confirm that annual mean wind speed is strongly related to the magnitude of the surface slope. The high elevation of the ice sheet south of the mountains makes for a dry, cold climate, in which mass loss owing to sublimation is small and erosion of snow by the wind has a potentially large impact on the surface mass balance. A simple katabatic-wind model is used to explain the variations of accumulation along the traverse line in terms of divergence/convergence of the local transport of drifting snow. The resulting wind- and snowdrift patterns are closely connected to the topography of the ice sheet: ridges are especially sensitive to erosion, while ice streams and other depressions act as collectors of drifting snow.
Keywords: Dronning Maud Land; NARE 1996/97; fysisk geografi; glasiologi; klimatologi; meteorologi